If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + 8)(a + 2) = 0 Reorder the terms: (8 + a)(a + 2) = 0 Reorder the terms: (8 + a)(2 + a) = 0 Multiply (8 + a) * (2 + a) (8(2 + a) + a(2 + a)) = 0 ((2 * 8 + a * 8) + a(2 + a)) = 0 ((16 + 8a) + a(2 + a)) = 0 (16 + 8a + (2 * a + a * a)) = 0 (16 + 8a + (2a + a2)) = 0 Combine like terms: 8a + 2a = 10a (16 + 10a + a2) = 0 Solving 16 + 10a + a2 = 0 Solving for variable 'a'. Factor a trinomial. (8 + a)(2 + a) = 0Subproblem 1
Set the factor '(8 + a)' equal to zero and attempt to solve: Simplifying 8 + a = 0 Solving 8 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + a = 0 + -8 Combine like terms: 8 + -8 = 0 0 + a = 0 + -8 a = 0 + -8 Combine like terms: 0 + -8 = -8 a = -8 Simplifying a = -8Subproblem 2
Set the factor '(2 + a)' equal to zero and attempt to solve: Simplifying 2 + a = 0 Solving 2 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + a = 0 + -2 Combine like terms: 2 + -2 = 0 0 + a = 0 + -2 a = 0 + -2 Combine like terms: 0 + -2 = -2 a = -2 Simplifying a = -2Solution
a = {-8, -2}
| (x^2-x-1)(x^2-x-1)=5+x^3 | | (x^2-x-1)=5+x^3 | | (x^2-x-1)=5+x | | 7+4(3v-4)=-3(3v-3)+7v | | 4x-15=2x+9 | | x^7+2x^6-5x^5-13x^4-13x^3-5x^2+2x+1=0 | | 9w^2-75w-54= | | 5y-3=4(y+3) | | (8x+9)(2x+4)=0 | | 5n+3+9= | | 3d^2-13d+12= | | r+(-2)=-8 | | 3=8-x | | -3b+7=8b-3 | | x^2=52-9x | | 7u+3-2(-2u-3)=2(u-3) | | z^4=-16i | | -4x+2=-7x+11 | | 3x(5x+36)=180 | | -16s-126+4(4s+32)=0 | | 8.1=x-12.5 | | 4x-8=x-5+3x | | 4x+2(-2x+7)=16 | | 16t^2+35t+5=0 | | 37-15x=8 | | 2x+0.33x=21 | | 13=-4t | | 4a-8whena=6 | | (5+4)[3+(8+5)]= | | 5z-13=-4z+14 | | 3x+12=6x-9x-12 | | 4(8-d)-50=20d-6(3+4d) |